(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Introduction: Visual inspection of cervix after application of 3-5% acetic acid (VIA) is a potential alternative to Pap smear cytology for screening of cervical cancer in resource poor settings. VIA has gained popularity and proven itself in many clinical trials as an adequate screening test. VIA is an attractive alternative to Pap smears for its ease of use, low-cost and fewer physician visits. Currently VIA is done in tertiary level hospitals by trained health care providers to generalize its efficacy. Objective: The main objective of this study was to evaluate the efficacy of visual inspection based screening approach in the detection of precancerous & early cancerous lesions of the cervix. Materials and Methods: This study was done as a part of an ongoing screening program in Rajshahi Medical College Hospital from July 2008 to December 2009. VIA was carried out in 540 eligible women attending Gynae OPD for gynecological problems. The women underwent a complete clinical evaluation. Detection of well-defined, opaque, acetowhite lesion close to squamocolumnar junction (SCJ) or in transitional zone (TZ), well-defined circumferential, acetowhite lesions or dense acetowhitening of ulceroproliferative growth on the cervix constituted a positive VIA. All screened women evaluated by colposcopy and biopsy were taken from colposcopically suspected areas or in cases of VIA negative from different quadrants of the cervix. The final diagnosis was based on histology, which allowed direct estimation of sensitivity, specificity, and predictive values of VIA. Those with CIN I or cancerous lesions diagnosed by histology were considered as true positive. Results: Out of 540 patients screened, 328(61%) were VIA negative and 212(39%) were VIA positive. Out of positive cases 87 (41%)%) seemed to have pathology. Colposcopy yielded normal results in 340 (63%) cases, low grade CIN in 138 (26%) cases, high grade CIN in 44 (8%) cases and cancer in 18 (3%) cases making total 200 cases. Of the 200 (37%) patients with positive colposcopy, 98 (49%) turned out to be negative on histology. There were biopsy proven chronic cervicitis and metaplastic changes in 423 (78%) cases, CIN I in 66 (12%) cases, CIN II in 25 (5%) cases, CIN III/ carcinoma-in-situ in 5 (1%) cases. Eighteen (3%) cases of cervical carcinoma were diagnosed on colposcopy but ultimately 21(21%) cases of invasive cancer were detected on histology. The sensitivity of VIA for biopsy proven CIN I was 74.36%, specificity 75.8%, positive predictive value 41.04%, & negative predictive value 90.85%. Conclusion: VIA can differentiate a normal cervix from a precancerous cervix with reasonable accuracy. Till now a good number of studies had been carried out in different countries of the world and now it is well established that the sensitivity of VIA equaled or exceeded the reported rates for conventional cervical cytology. As it is low cost and simple method, it can be set in any hospital or any health care centre of rural or urban areas of poor resource settings. Bangladesh J Obstet Gynaecol, 2013; Vol. 28(1) : 31-37